The Effect of Stocking Densities on Mortality of Nile Tilapia (Oreochromis niloticus) Fingerlings (3-5 cm) in a Closed Wet Transportation System from Kediri to Sidoarjo - Fathonah; Sri Oetami Madyowati; Achmad Kusyairi (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2026)
Transportation of fish fingerlings is an important stage in aquaculture activities because it affects the success of fingerlings distribution. One of the factors influencing transportation success is stocking density during transportation. This study aimed to determine the effect of different stocking densities on the mortality of Nile tilapia (Oreochromis niloticus) fingerlings (3-5 cm) in a closed wet transportation system and determine the stocking density resulting in the lowest mortality rate. This study used an experimental method with a Completely Randomized Design (CRD) consisting of four treatments: A (100 fish/5 L), B (120 fish/5 L), C (150 fish/5 L), and D (200 fish/5 L) with six replications. Transportation was conducted for four hours with a water-to-oxygen ratio of 1:3. Parameters observed included mortality, survival rate, temperature, and pH. The results showed that stocking density affected the mortality of Nile tilapia fingerlings. The lowest mortality was observed in treatment A (1.83%), while the highest mortality was found in treatment D (7.83%). A density of 100 fish/5 L provided the best condition for minimizing mortality during transportation.